The Relationship of Mindfulness, Inner speech and Gender - HUSSAIN, IJAZ; SHAH, ASGHAR ALI (International Journal of Psychosocial Rehabilitation, 2020)
The relationship of mindfulness, Inner speech and gender was investigated in the current study by administering Self-Talk Scale and Mindful Attention and Awareness Scale to four hundred participants (N=400) consisted of both genders (male, 225; female, 175), with the age limit of 20-40 years. The sample was taken from Islamic International University, Islamabad and University of Peshawar, Pakistan and analyzed by applying t-test and regression analysis. The findings of the study showed that mindfulness was negatively related to the frequency of inner speech. Self criticism and social assessment inner speech were found to be negatively related to mindfulness. Women were found to be more mindful compared to men. Women also scored higher compared to men on social assessment inner speech.